2016
DOI: 10.21502/limuj.006.01.2016
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive retrospective study on children with newly diagnosed nephrotic syndrome presented to Tripoli Children Hospital during the period between Jan. to Dec. 2014

Abstract: Introduction: Nephrotic syndrome (NS) is a clinical picture characterized by severe proteinuria, hypoalbuminemia, edema and hypercholesterolemia. A retrospective study was carried out in order to describe disease pattern in newly diagnosed NS of children admitted to Tripoli children hospital during the year 2014. Methods: The medical data of 56 patients aged between 1 year and 11 years diagnosed with idiopathic nephrotic syndrome were analysed using SPSS software. The data included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…The current study showed age of cases was 2.8-8 years in group I and 3.5-6 years in group II. This is in agreement with Rhuma et al (11) who reported that INS is a disease of pre-school aged children with peak age incidence of 2-3 years. Also, Saraswathi et al (12) who reported that childhood NS can occur at any age but is most common between the ages of 1.5 and 5 years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study showed age of cases was 2.8-8 years in group I and 3.5-6 years in group II. This is in agreement with Rhuma et al (11) who reported that INS is a disease of pre-school aged children with peak age incidence of 2-3 years. Also, Saraswathi et al (12) who reported that childhood NS can occur at any age but is most common between the ages of 1.5 and 5 years.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed obvious male predominance (64.3% in group I and 60% in group II) which is supported by Rhuma et al (11) and Ephraim et al (13) who reported that INS affected males more than females. Current study showed no significant difference among studied as regard age and sex.…”
Section: Discussionsupporting
confidence: 88%
“…During the study of the sex distribution in our patients, we found male predominance (60%). Rhuma et al, [10] and Ephraim et al, [11] similarly reported that INS affected males more than females.…”
Section: Discussionmentioning
confidence: 95%